Influence of classroom indoor environmental quality on student satisfaction - Ainul Zuhairi, Ainul Jasmeen; Mohd Puad, Mohd Hazwan (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
The purpose of this study is to investigate the relationship between classroom environmental quality of Polytechnic and student satisfaction. This study also investigates which indoor environmental factors which comprises lighting, acoustics, temperature, and air quality influence student satisfaction of the learning environment the most. This study is relevant because previous research has shown that when students feel satisfied with their classroom indoor environmental quality, better outcomes can be achieved. This is in line with Malaysian education objective which is to maximise student outcomes. It also allows the institution to make improvement on the quality of classrooms indoor environment and enhance its sustainability. The expected result is that classroom indoor environmental quality does influence student satisfaction and temperature affects students the most.